PENGARUH MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN DI GH UNIVERSAL HOTEL BANDUNG - Imas Wiwin Kurniasih; Zein Bastian; Hedi Setiadi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2023)
The performance index of active employees who worked at GH Universal Hotel Bandung from 2016 to 2019 showed a decline, one of the factors suspected to be the cause of the decline in employee performance, namely Achievement Motivation because the achievement of absentee targets did not increase. or considered static for 4 years from 2015. 2016 to 2019. This study aims to determine the effect of achievement motivation on employee performance at GH Universal Hotel Bandung. The object of research is permanent and contract employees who work at GH Universal Hotel Bandung in 2020, from a population of 138 employees 103 samples were taken, data collection was carried out by distributing questionnaires to respondents with the method used in this study is a quantitative method and the type of descriptive verification method using simple linear regression analysis. The results showed that there was a positive and significant influence between achievement motivation and employee performance at GH Universal Hotel Bandung.